Rheological Properties of Corn Starch Gels With the Addition of Hydroxypropyl Methylcellulose of Different Viscosities - Montes, Leticia; Rosell, Cristina M.; Moreira, Ramón (Frontiers in Nutrition, 2022)
The objective of this study is to determine the effect of the addition of hydroxypropyl methylcellulose (HPMC) (from 0.5 to 2.0% w/w, starch basis) with three different viscosities (40–60, 80–120, and 2,600–5,600 mPa⋅s) to corn starch (30% w/w, total basis) gels. Average viscosimetric molecular weights (Mv) of tested HPMC were determined (from 27.2 × 103 to 82.7 × 103 g/mol). Water retention capacity of HPMC varied linearly with Mv. The formation and curation of gels were monitored by rheology employing consecutive steps such as heating ramp (25–90°C), time sweep (90°C), cooling ramp (90–25°C), time sweep (25°C), and frequency sweep. Additionally, creep-recovery tests were performed. HPMC above 1.5% w/w delayed the range of gelatinization temperature of starch up to 2°C. Viscoelasticity and stiffness of corn starch gels with HPMC depend on both the amount of polymer added and Mv of the HPMC. Finally, to achieve corn gels with mimetic viscoelastic properties to wheat gel (with constant total solids), HPMC with relatively low viscosity (low Mv) is necessary to be added at certain content.